KEPEMIMPINAN KHARISMATIK KIAI DAN IMPLIKASINYA TERHADAP KECERDASAN SPIRITUAL SANTRI - Fuzi Fauziah; Moh. Syamsul Falah (Program Studi Manajemen Pendidikan Islam, 2025)
The charismatic leadership of kiai plays a strategic role in shaping the character and spirituality of santri in Islamic boarding schools. This study aims to analyze the influence of kiai's charismatic leadership on the spiritual intelligence of santri at Pondok Pesantren Darul Falah 5 Cukir Jombang. This research uses a qualitative approach with a case study method. Data were collected through participatory observation, in-depth interviews, and documentation. Research subjects include kiai, ustadz, and senior and junior santri. Data analysis used qualitative descriptive analysis. The results showed that the charismatic leadership of kiai at Pondok Pesantren Darul Falah 5 Cukir Jombang is reflected through spiritual exemplary, wisdom in decision making, inspirational communication skills, and high dedication to Islamic education. This leadership has positive implications for improving santri's spiritual intelligence which includes self-awareness, spiritual reflection ability, empathy, and commitment to religious values. The conclusion of this study shows that the charismatic leadership of kiai plays a significant role in developing santri's spiritual intelligence through the process of internalizing spiritual values in daily life